Effects of time-restricted nutrition on urinary density, body composition and athletic performance: model ramadan fast - Dündar, Sibel Tetik (2023)
Objective: This study has been carried out in order to study the effects of the Ramadan fast which is one of the time-restricted nutritional models on the urinary density, body composition athletic performance. Twenty-seven students whose age average is 20,57±1,59, doing sports for recreational purposes, participated in the research. All participants recorded all the food which they took during the hours between the breaking and starting times of fasting when having food is allowed during the month of Ramadan. At the same time, the amount of water consumed, exercising and sleeping times, number of cigarettes smoked were recorded as well. In determining the somatotypes, a skinfold caliper, a tape and a digital compass were used in order to measure skin fold thickness, perimeter and diameter respectively. Body mass, fat, muscle, bone and water rates were measured by means of a digital body analysis scale. Urine chemistry was measured by the reflectance photometry method. A WAnT and Yo-Yo intermittent recovery test were performed in order to determine the anaerobic power level and the aerobic power level respectively. Consequently, fasting may be a benefit for either the reduction or stopping of cigarette smoking. At the same time, effective results may be obtained in losing weight despite the biological rhythm.  This study shows that anaerobic power of those who fast increases while their aerobic power reduces.